Analysis of System Quality Factors & Information Quality with Mediation Variables of Ease of Use To the Success of PT XYZ's E-Procurement - Kenny Hardinata; Mentiana Sibarani (Green Publisher Indonesia, 2024)
This study examines the influence of system quality and information quality on the success of e-procurement at PT XYZ, with a focus on the mediating role of ease of use. Data were collected from 42 respondents in the purchasing department, all users of the e-procurement system, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Key findings include that system quality and information quality both positively affect ease of use. High-quality systems and accurate information make the e-procurement system easier to use. Information quality also directly enhances the success of e-procurement. Additionally, ease of use positively impacts the success of the system, indicating that when users find the system easy to use, its success rate increases. While system quality alone does not directly impact success, it does so when combined with high information quality and ease of use. For PT XYZ, these findings suggest that improving system quality and information quality can significantly enhance e-procurement success. Practical steps include ensuring robust internet connectivity, comprehensive data documentation, timely updates, and clear, accurate information. Simplifying the e-procurement process and enhancing user skills will also contribute to more effective and efficient procurement operations.